Regulation of vascular smooth muscle mechanotransduction by microRNAs and L-type calcium channels - Turczyńska, Karolina M. (Landes Bioscience, 2013)
The phenotype of smooth muscle cells is regulated by multiple environmental factors including mechanical forces. Mechanical stretch of mouse portal veins ex vivo has been shown to promote contractile differentiation by activation of the Rho-pathway, an effect that is dependent on the influx of calcium via L-type calcium channels. MicroRNAs have recently been demonstrated to play a significant role in the control of smooth muscle phenotype and in a recent report we investigated their role in vascular mechanosensing. By smooth muscle specific deletion of Dicer, we found that microRNAs are essential for smooth muscle differentiation in response to stretch by regulating CamKIIδ and L-type calcium channel expression. Furthermore, we suggest that loss of L-type calcium channels in Dicer KO is due to reduced expression of the smooth muscle-enriched microRNA, miR-145, which targets CamKIIδ. These results unveil a novel mechanism for miR-145 dependent regulation of smooth muscle phenotype.